Landline - Rowell, Rainbow (New York St. Martin's Press, 2014)
"The magic phone becomes Ms. Rowell's way to rewrite 'It's a Wonderful Life'...what that film accomplished with an angel named Clarence, Ms. Rowell accomplishes with a quaint old means of communication, and for her narrative purposes, it really does the trick." -The New York Times. "While the topic might have changed, this is still Rowell--reading her work feels like listening to your hilariously insightful best friend tell her best stories." -Library Journal, starred review on Landline. "Her characters are instantly lovable, and the story moves quickly...the ending manages to surprise and satisfy all at once. Fans will love Rowell's return to a story close to their hearts." -Kirkus Reviews on Landline
English stories
2
Keywords: English stories